Kompatibilitas Sumber Inokulan Fungi Mikoriza Arbuskular pada Kedelai dengan Budidaya Jenuh Air - Muis, Ridwan; Ghulamahdi, Munif; Melati, Maya; Purwono, Purwono; Mansur, Irdika (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
The main problem encountered by soybean crop in acid sulfate tidal lands is less availability of P, because of its chemical bond with Fe. Heavy dose of  fertilization often lead to high fertilizer residue, wich could be used for crops farming using AMF. Research was conducted to study the effect of soybean culturing technique and AMF inoculants source on growth of  soybean. The treatments consisted two factors, arranged in a randomized block design with three replications. The first factor was four inoculants sources of AMF, namely AMF and without inoculation AMF, inoculants from rhizospheres of kudzu (Pueraria javanica), sorghum (Sorghum bicolor), corn (Zea mays) and soybean (Glycine max). The second factor was culturing tehnique, namely water saturated and dry soil culture. Soybeans were grown in pots containing 5 kg soil derived from tidal land,  Simpang Village, District of Berbak, East Tanjung Jabung Regency,  Jambi Province. Results showed that the interaction saturated soil culture with inoculants from corn’s rhizosphere had positive effect on the variability of N, P and K uptake, N and P content in the plant, relative efficiency of inoculants and relative efficiency of P uptake, stem diameter, biomass dry weight, the number of filled pods and seed dry weight of soybeans. Dry soil culture with inoculants of corn’s rhizosphere had greater root colonization, but overall for the growth and grain yield of soybean, saturated soil culture with inoculants from corn rhizosphere has better effect on other growth variables.